Long-term trends in nitrogen oxides concentrations and on-road vehicle emission factors in Copenhagen, London and Stockholm. (1st December 2021) - Krecl, Patricia; Harrison, Roy M.; Johansson, Christer; Targino, Admir Créso; Beddows, David C.; Ellermann, Thomas; Lara, Camila; Ketzel, Matthias
Abstract: Road transport is the main anthropogenic source of NOx in Europe, affecting human health and ecosystems. Thus, mitigation policies have been implemented to reduce on-road vehicle emissions, particularly through the Euro standard limits. To evaluate the effectiveness of these policies, we calculated NO2 and NOx concentration trends using air quality and meteorological measurements conducted in three European cities over 26 years. These data were also employed to estimate the trends in NOx emission factors (EFNOx, based on inverse dispersion modeling) and NO2 :NOx emission ratios for the vehicle fleets under real-world driving conditions. In the period 1998–2017, Copenhagen and Stockholm showed large reductions in both the urban background NOx concentrations (−2.1 and −2.6% yr −1, respectively) and EFNOx at curbside sites (68 and 43%, respectively), proving the success of the Euro standards in diminishing NOx emissions. London presented a modest decrease in urban background NOx concentrations (−1.3% yr −1 ), while EFNOx remained rather constant at the curbside site (Marylebone Road) due to the increase in public bus traffic. NO2 primary emissions —that are not regulated— increased until 2008–2010, which also reflected in the ambient concentrations. This increase was associated with a strong dieselization process and the introduction of new after-treatment technologies that targeted the emission reduction of other species (e.g., greenhouse gases or particulate matter). Thus, while regulations on ambient concentrations of specific species have positive effects on human health, the overall outcomes should be considered before widely adopting them. Emission inventories for the on-road transportation sector should include EFNOx derived from real-world measurements, particularly in urban settings. Graphical abstract: Image 1 Highlights: NOx and NO2 reductions were seen in the background of the three cities in 1998–2017. NO2 primary emissions increased until 2010 due to vehicle after-treatment systems. EFNOx of the vehicle fleet decreased in Copenhagen (68%) and Stockholm (43%). London showed the smallest reductions in ambient concentrations and EFNOx . EFNOx was consistent with on-road studies but higher than simulated by emission models.